BOOK REVIEW: THE CONCEPT OF MIND By Gilbert Ryle. Prescott: Peregrine Book Company, 1963. Pp. 311. ISBN 140550291 (Hardcover). 25. Reviewed by Samuel Princewill Asuquo - Asuquo, Samuel Princewill (African Journal of Social and Behavioural Sciences, 2025)
The philosophical theory that divides the mind and body into separate entities, known as Cartesian dualism, is profoundly contested by Gilbert Ryle’s groundbreaking 1949 work The Concept of Mind. By presenting the idea of the "category mistake," Ryle challenges this viewpoint, contending that mental processes are visible patterns of behaviour rather than hidden, internal systems. By redefining mental states as inclinations to behave in particular ways, his approach provides a paradigm that unifies conduct and thought. Ryle’s views are examined in detail in this study, with a focus on their applicability to forensic and correctional psychology. Other scholars’ critiques and opposing viewpoints are also discussed.